Penerapan Protokol Kesehatan pada Masyarakat Sukodono dalam Perspektif Islam dan Sosial Kemasyarakatan - Khanjun Azenno; Aldorama Satriagung Aziz; Imamul Arifin (JIE (Journal of Islamic Education), 2022)
This study aims to open the community's mindset to their response to Covid-19 from the point of view of Islam, social society, and science to end the Covid-19 pandemic. This research uses qualitative methods and case studies. The data were obtained from the results of surveys, interviews, observations, and analysis of the substance under investigation and added data from the literature as a reference. The study results show that people's mindsets can affect the spread of the Covid-19 virus because this wrong mindset will result in those who underestimate the virus so that it spreads more widely. Therefore, it is necessary to instil an understanding that ending this pandemic requires an open mind to all solutions provided by the government because the government always provides the best solutions for its people, such as implementing Health protocols and vaccinations.